Predictors of Failure of Catheter Salvage in Incident Hemodialysis Patients. Issue 5 (May 2013) - Zhou, Zhou; Guo, Dongyang; Zhang, Fan; Wang, Tao; Zhang, Guangming
Purpose: Catheter-related bloodstream infection is a frequent complication for patients who use catheter as dialysis access. This study was performed to identify the risk factors for failed catheter salvage. Methods: We enrolled patients who received non-tunneled catheters as initial vascular access during a two-year period. Catheter salvage was attempted in all symptomatically mild patients. Patients were prospectively followed for 8 weeks starting from the day of infection. Risk factors for salvage failure were explored. Results: A total of 77 bacteremia episodes occurred in 69 patient, with an infection rate of 1.61 per 1, 000 catheter days. Salvage was successful in 73.4% of all episodes. We found that higher ferritin levels (greater vs. lower than 500 mg/l, (odds ratio (OR) 6.388, 95% confidence interval (CI) 2.073, 19.686), higher phosphate levels (greater vs. lower than 5.5 mg/dl, OR 4.084, 95% CI 1.391, 11.978) and shorter time intervals between catheterization and infection (within vs. beyond 3 weeks, OR 4.190, 95% CI 1.279, 13.725) predicted salvage failure. Conclusions: Catheter salvage can be a reasonable initial strategy for symptomatically mild patients. We propose salvaging aggressively and waiting watchfully; however, clinical judgment is prior to any specific management protocol.